Melanosis Coli - Suharno Hakim; Putut Bayupurnama; Neneng Ratnasari (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2016)
Melanosis coli is a brownish discoloration of the colonic mucosa caused by the accumulation of pigment in macrophages of the lamina propria. We reported a 62 years old woman with prolonged constipation since 10 years ago. She underwent haemorhoidectomy when 17 years old. Since 4 years ago she regularly comsumted herbal laxative. On 27 january 2015 underwent colonoscopy at Sardjito hospital Yogyakarta. Colonoscopic examination revealed Melanosis coli.